2022
DOI: 10.1021/acs.jafc.2c00335
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Different Milk Constituents in Modulating the Gut Microbiome and Infant Health

Abstract: Human milk, the gold standard for optimal nourishment, controls the microbial composition of infants by either enhancing or limiting bacterial growth. The milk fat globule membrane has gained interest in gut-related functions and cognitive development. The membrane proteins can directly interact with probiotic bacteria, influencing their survival and adhesion through gastrointestinal transit, whereas membrane phospholipids increase the residence time of probiotic bacteria in the gut. The commensal bacteria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 228 publications
0
9
0
Order By: Relevance
“…The study concluded that lactoferrin showed significant promise in reducing the risk of respiratory tract infections and potential use as an adjuvant in COVID-19 infections [153]. Milk and its many components are known to improve gut microbiota [154]. Therefore, the beneficial effects of milk on COVID-19 could be associated with gut microbiota improvement and as such warrant further verification.…”
Section: Milkmentioning
confidence: 98%
“…The study concluded that lactoferrin showed significant promise in reducing the risk of respiratory tract infections and potential use as an adjuvant in COVID-19 infections [153]. Milk and its many components are known to improve gut microbiota [154]. Therefore, the beneficial effects of milk on COVID-19 could be associated with gut microbiota improvement and as such warrant further verification.…”
Section: Milkmentioning
confidence: 98%
“…Some bioactive components are also abundant in HM, such as anti-infective factors, immune components, and metabolic enzymes . Breast milk plays a crucial role in furnishing infants with indispensable nutrients necessary for their growth and development . Meanwhile, many animal milks have been studied in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…2 Breast milk plays a crucial role in furnishing infants with indispensable nutrients necessary for their growth and development. 3 Meanwhile, many animal milks have been studied in recent years. Interestingly, in terms of physicochemical characteristics, monogastric animal milks are more appropriate for human nutrition than ruminant milks.…”
Section: Introductionmentioning
confidence: 99%
“…Milk is rich in nutrients, and its consumption has several benefits for the organism, including growth promotion, modulation of immune response, prevention of gastrointestinal infections, and regulation of intestinal microflora. 1 , 2 , 3 Milk fat, lactose, and whey protein are the main nutrients in milk, of which milk fat is a natural fat produced by the mammary glands of dairy cows and is an important indicator for evaluating milk quality. 4 Mammary epithelial cells (MECs) are the functional unit of lactation in dairy cows' mammary glands, and the proliferative capacity of MECs and the ability to synthesize milk fat directly affect mammary gland development and lactation.…”
Section: Introductionmentioning
confidence: 99%